1990
DOI: 10.1038/eye.1990.54
|View full text |Cite
|
Sign up to set email alerts
|

The complications of trabeculectomy (a 20-year follow-up)

Abstract: SummaryThe complications of trabeculectomy were studied in two groups of patients taken from a stable white population. The first group who had had their operation when it was first introduced 22 years ago, had been previously treated with prolonged medi cation, the second group had been operated upon recently and had had short-term pre-operative medication. This study confirmed that trabeculectomy predictably reduces the intraocular pressure to within the accepted normal range and that the pressure level belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
1
12

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(149 citation statements)
references
References 25 publications
6
130
1
12
Order By: Relevance
“…Reassuringly, other long-term studies indicate little correlation between early complications and long-term outcome. 14 In our survey, a comparison was made between the consultants and HST. Although it was not formally documented, in terms of patient selection the consultants tended to perform the more complicated cases (ie only eyes, advanced glaucoma, etc.).…”
Section: Variablementioning
confidence: 99%
“…Reassuringly, other long-term studies indicate little correlation between early complications and long-term outcome. 14 In our survey, a comparison was made between the consultants and HST. Although it was not formally documented, in terms of patient selection the consultants tended to perform the more complicated cases (ie only eyes, advanced glaucoma, etc.).…”
Section: Variablementioning
confidence: 99%
“…Indeed, in a paper with the longest followup to date, Molteno reported that 42.9% of cases had lost more than one line of Snellen acuity and the probability of legal blindness was 0.4 at 15 years 20 and in Watson's 20-year follow-up paper more than two lines of Snellen acuity were lost in 30% of cases at final follow-up. 27 In this survey a significant number (18.8%) of patients had lost more than one line of bestcorrected Snellen acuity by 1 year after trabeculectomy. In a third of these cases no reason was given for the loss of acuity (Table 2).…”
Section: Late Complicationsmentioning
confidence: 99%
“…In a study of 150 eyes which had undergone unaugmented trabeculectomy with 9-year follow-up (predominantly white patients), 90% were controlled (IOPo20 mmHg no medication) at the last visit. 28 Chen et al 29 retrospectively reported a series of patients with various glaucoma diagnoses from a mixed white and black population, who underwent unaugmented primary trabeculectomies. In all, 40 patients were identified who had successful IOP control at 1 year (IOPo21 mmHg or 33% reduction).…”
Section: Introductionmentioning
confidence: 99%